(untitled) (Research, Society and Development, 2023)
The concept of plant blindness deals with the human inability to perceive the plants around, although they are essential for the basis of life on Earth. Furthermore, the daily human coexistence with plants or with products derived from plants is indisputable. We look for strategies to reverse the perceptive capacity of plants in our daily lives, bringing the Scientia amabilis; to the foreground, focusing on Botany as a fundamental area of Biological Sciences. We proposed to undergraduate students of Biological Science the production of a botany notebook in which they record their daily experiences with plants and plant-derived products. The activity was carried out in four steps: (1) production of the text; (2) a conversation circle; (3) insertion of scientific botanical data in the notebooks; and (4) analysis of the notebook text contents. The relationships established by the students focused on the utilitarian perception. The scientific approaches followed mostly the logic of the textbooks, with emphasis on plant structures, followed by plant systematics and physiology. The analysis of the texts and the narrative of the students allows us to conclude that the production of the Botany Notebooks improved the students’ perception the importance of plants for human survival and served as a trigger for interest in discussions of botanical the environmental balance and the maintenance of all levels of life on Earth.